Emerging Approaches of Transcatheter Valve Repair/Insertion - Maurizio Taramasso; Micaela Cioni; Andrea Giacomini; Iassen Michev; Cosmo Godino; Matteo Montorfano; Antonio Colombo; Ottavio Alfieri; Francesco Maisano (Cardiology Research and Practice)
Aortic stenosis (AS) and mitral regurgitation (MR) account for the majority of valvular diseases and their prevalence is increasing according to increased life expectancy. Surgical treatment is the gold standard, although operative risk may be high in some patients due to comorbidities and age. A large part of the patients at high surgical risk who could beneficiate of treatment are not referred to surgery. Therefore, there is a need of alternative and less invasive procedures.